Clinical evaluation of the refined clothespin relocation test: A pilot study. (October 2019) - Hussaini, Ali; Hill, Wendy; Kyberd, Peter
Background: The refined clothespin relocation test is a test used to evaluate the performance of a prosthesis user by analysing the compensatory motions and time to complete a grasping and placement exercise. The test has been studied previously with a motion capture laboratory and has now been adapted for a clinical setting. A comparison of prosthesis user to an able-bodied group is needed to determine efficacy as an assessment tool. Objective: To modify the previous refined clothespin relocation test and assess whether it can distinguish between able-bodied and prosthesis users. Study design: Comparative analysis. Methods: Forty-two able-bodied subjects and three prosthesis users completed the adapted refined clothespin relocation test protocol. Average refined clothespin relocation test scores describing the degree of compensatory movements and the time to complete the protocol were compared using a Mann–Whitney U-test. Results: A significant difference was found in the refined clothespin relocation test score between the able-bodied (Md = 65.32, n  = 42) and prosthesis users (Md = 23.07, n  = 3) with a medium effect size ( p  < 0.001, r  = 0.43). Conclusion: Prosthesis users demonstrated larger compensations and longer completion times, as reflected in the refined clothespin relocation test final score. The refined clothespin relocation test has the potential to be a useful clinical tool to assess user performance on a functional task. Clinical relevance: This preliminary study demonstrates that the adapted protocol can distinguish between the two groups based on refined clothespin relocation test score. A future multi-centre study is required using multiple raters and comparing it with the existing outcome measures to validate the refined clothespin relocation test and determine inter-rater reliability.